2014
DOI: 10.1007/s00330-013-3090-9
|View full text |Cite
|
Sign up to set email alerts
|

Image quality assessment of ultra low-dose chest CT using sinogram-affirmed iterative reconstruction

Abstract: • Iterative reconstruction enables ultra-low-dose CT (ULDCT) with very low radiation doses. • Image quality of ULDCT depends on the patient body mass index (BMI). • Selection of kVp and mAs depends on both BMI and lesion type. • Diagnosis of pulmonary emphysema or ground-glass nodules requires higher radiation doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 23 publications
6
43
0
Order By: Relevance
“…With developments of iterative reconstruction technology, newer iterative reconstruction algorithms allow unenhanced chest CT with much lower radiation doses [5,8,9,16]. In studies of chest CT using iterative reconstruction, Lee et al [9] reported that ultralow-dose CT (effective radiation dose, 0.29 mSv) yielded diagnostic-quality images in 91% of cases, and Neroladaki et al [8] reported that ultra-low-dose CT using a radiation exposure similar to chest x-ray examination (0.16 mSv) was diagnostic for pulmonary nodules. In the current study, overall image quality assessment using normal pulmonary structures was of diagnostic quality in 96% of scans for ultra-low-dose CT protocol A (0.44 mSv) and 88% of scans for ultra-low-dose CT protocol B (0.31 mSv).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With developments of iterative reconstruction technology, newer iterative reconstruction algorithms allow unenhanced chest CT with much lower radiation doses [5,8,9,16]. In studies of chest CT using iterative reconstruction, Lee et al [9] reported that ultralow-dose CT (effective radiation dose, 0.29 mSv) yielded diagnostic-quality images in 91% of cases, and Neroladaki et al [8] reported that ultra-low-dose CT using a radiation exposure similar to chest x-ray examination (0.16 mSv) was diagnostic for pulmonary nodules. In the current study, overall image quality assessment using normal pulmonary structures was of diagnostic quality in 96% of scans for ultra-low-dose CT protocol A (0.44 mSv) and 88% of scans for ultra-low-dose CT protocol B (0.31 mSv).…”
Section: Discussionmentioning
confidence: 99%
“…Many reports on iterative reconstruction of chest CT have appeared, showing that iterative reconstruction reduces noise and improves both objective and subjective imaging quality, compared with filtered back projection (FBP), when the same radiation dose is delivered [2][3][4][5][6][7]. However, few studies have investigated the utility of ultra-low-dose acquisitions for assessment of pulmonary lesions [3,8,9].The purpose of the current study was to evaluate the image quality and radiation dose reduction of ultra-low-dose CT scans processed using a sinogram-affirmed iterative reconstruction algorithm (SAFIRE) [10]. C a r d io p u l m o n a r y I m ag i ng • O r ig i n a l R e s e a rc h…”
mentioning
confidence: 97%
“…Comparison of different dose levels in the same patient was achieved by using data from only one detector of a dual source CT scanner (n = 2) [24,25], using a previously made scan (n = 2) [17,26], comparing the scan non contrast-enhanced scan with the contrast-enhanced scan (n = 1) [27] or by making one (n = 7) [6,18,19,22,[28][29][30] two (n = 2) [20,21] or four (n = 1) [31] additional scans for research purposes. The indication for chest CT varied widely.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Another population, namely that of pregnant women, should also benefit from iterative reconstructions as a powerful means to provide diagnostic examinations while reducing the dose to the foetus as well as the mother's breast tissue. Several studies have recently shown that iterative reconstruction is a promising option to reduce radiation exposure without compromising the image quality of chest CT examinations [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%